PPADS: an antagonist at endothelial P2Y-purinoceptors but not P2U-purinoceptors. - Brown, C. (1995)
1. Bovine aortic endothelial (BAE) cells contain two co-existing receptors for extracellular ATP, the P2Y and P2U-purinoceptors. Here we have determined whether the proposed P2X-purinoceptor antagonist, pyridoxalphosphate-6-azophenyl-2', 4'-disulphonic acid (PPADS) could distinguish between these two receptor subtypes. 2. Cells labelled with myo-[2-3H]-inositol were stimulated with increasing concentrations of either the P2Y-agonist, 2MeSATP, or the P2U-agonist, UTP in the absence or presence of 30 microM PPADS. The accumulation of total [3H]-inositol (poly)phosphates mediated by 2MeSATP was markedly attenuated by PPADS, whereas the response to UTP was not significantly affected. 3. Stimulation of BAE cells with increasing concentrations of ATP showed a reduced response in the presence of 10 microM PPADS, but this effect of the antagonist was not significant. By contrast, inhibition of the response to ADP was profound and highly significant. 4. These observations show that PPADS is not a selective P2X-purinoceptor antagonist, but is able to distinguish between P2Y- and P2YU-purinoceptors in BAE cells, and indicate that this compound may provide a useful tool in the study of multiple subtypes of P2-purinoceptors. Furthermore the results are consistent with the hypothesis that ATP interacts with both receptor subtypes, but that the action of ADP is primarily at the P2Y-purinoceptor in these endothelial cells.